Fields, power, and social skill: a critical analysis of the new institutionalisms - Fligstein, Neil (Экономическая социология, 2010)
"New Institutional" Theories have proliferated across the social sciences. While they have substantial disagreements, they agree that institutions are created to produce local social orders, are social constructions, fundamentally about how powerful groups create rules of interaction and maintain unequal resource distributions, and yet, once in existence, both constrain and enable actors in subsequent institution building. I present a critique of these theories that focuses on their inadequate attention to the role of social power and actors in the creation of institutions. An alternative view of the dynamics of institutions is sketched out based on a more sociological conception of rules, resources, and social skill.